2019
DOI: 10.1093/geront/gny178
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Function With Driving Space and Crashes Among Older Adults

Abstract: Background and Objectives Balancing both driver mobility and safety is important for the well-being of older adults. However, research on the association of physical function with these 2 driving outcomes has yielded inconsistent findings. This study examined whether physical functioning of older drivers, as measured by the Short Physical Performance Battery (SPPB), is associated with either driving space or crash involvement. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…Given previous research, the finding that those with higher levels of the frailty phenotype are more likely to be classified as low-mileage drivers implies that measures of the frailty phenotype may also be used to identify older adults who are more likely to be involved in car crashes. This implication is supported by previous research on the AAA LongROAD cohort by Man et al (2020), which found that being classified as nonfrail was protective against having a self-reported crash rate of one or more crashes in the previous year [29]. If true, this means interventions that aim to reduce the prevalence of frailty may be successful in helping older adults increase their driving exposure [30,31], decrease their overall crash rate, and maintain their driving independence by delaying driving cessation.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Given previous research, the finding that those with higher levels of the frailty phenotype are more likely to be classified as low-mileage drivers implies that measures of the frailty phenotype may also be used to identify older adults who are more likely to be involved in car crashes. This implication is supported by previous research on the AAA LongROAD cohort by Man et al (2020), which found that being classified as nonfrail was protective against having a self-reported crash rate of one or more crashes in the previous year [29]. If true, this means interventions that aim to reduce the prevalence of frailty may be successful in helping older adults increase their driving exposure [30,31], decrease their overall crash rate, and maintain their driving independence by delaying driving cessation.…”
Section: Discussionmentioning
confidence: 53%
“…Depression was scored using the Patient-Reported Outcomes Measurement Information System (PROMIS) instruments, with higher scores indicative of more severe depression [20]. Cognitive health was assessed by performance on immediate and delayed word recall tasks, which are designed to test episodic and working memory, with higher scores indicative of better cognitive health [21,22]. To measure driving importance, participants were asked "How important is it that you continue driving?".…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the Short Physical Performance Battery (SPPB), a tool that includes static and dynamic balance, gait speed, and repeated chair stands [48] is not included in the mentioned reviews. SPPB scores are predictive of community-dwelling older adults who are at risk for falls [49,50], who might suffer from higher all-cause mortality [51], as well as at-risk drivers who are likely to be in motor vehicle accidents [52]. The SPPB may be a very useful tool for outpatient oncology nurses in identifying older patients who are at risk for falls.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-frail participants had 30% higher odds of reporting involvement in a crash in the prior year than non-frail participants after adjusting for several confounding factors [198]. In a recent Japanese study [199], 349 older drivers were classified in a (pre-)frail and a robust group. Pre-frailty/frailty was associated with more nearmiss traffic incidents compared to robustness.…”
Section: Frailtymentioning
confidence: 99%